The association between body mass index and live birth and maternal and perinatal outcomes after in-vitro fertilization: a national cohort study - Kluge, Linda; Källén, Karin; Thurin-Kjellberg, Ann; Wennerholm, Ulla-Britt; Bergh, Christina (Frontiers in Endocrinology, 2023)
Objective: To investigate the association between female body mass index (BMI) and live birth rates and maternal and perinatal outcomes after in vitro fertilization (IVF).We performed a national, population-based cohort study including women undergoing IVF between 2002 and 2020. The cohort included 126 620 fresh cycles and subsequent frozen embryo transfers between 2007 and 2019 (subpopulation 1) and 58 187 singleton deliveries between 2002 and 2020 (subpopulation 2). Exposure was female BMI (kg/m 2 ) categorised according to the World Health Organisation: underweight (<18.5), normal weight (18.5-24.9, reference), overweight (25.0-29.9), class I obesity (30.0-34.9), class II obesity (35.0-39.9), and class III obesity (≥40.0). Primary outcome in subpopulation 1 was cumulative live birth per started fresh IVF cycle, including fresh and subsequent frozen embryo transfers. Primary outcomes in subpopulation 2 were hypertensive disorders of pregnancy and preterm birth at less than 37 weeks. Risk ratios (RR) with 95% confidence interval (CI) for the association between BMI class and the outcomes were calculated using generalised linear models with adjusted for relevant confounders.The cumulative live birth rate decreased significantly with increasing BMI from 32.6% in normal weight women to 29.4% in overweight women, 27.0% in women in obesity class I, 21.8% in This is a provisional file, not the final typeset article women in obesity class II, and 7.6% in women in obesity class III. The risk of hypertensive disorders of pregnancy increased significantly and progressively with increasing BMI, from 4.6% in normal weight women to 7.8% in overweight women and 12.5%, 17.9%, and 20.3% in women in obesity classes I, II, and III. The risk of preterm birth followed a similar pattern, from 6.3% in normal weight women to 7.5% in overweight women and 8.9%, 9.9%, and 15.3% in women in obesity classes I, II, and III. Risks of other perinatal complications, such as perinatal death, showed an even more pronounced increase.Conclusions: Using a large and complete national cohort of women undergoing IVF, we demonstrate a dose dependent decrease in live birth rate and a substantial increase in maternal and perinatal complications with increasing BMI. Strategies to improve this situation are warranted.